2020
DOI: 10.3390/met10111422
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Casting Conditions for Reduced Pressure Test on Melt Quality of Al-Si Alloy

Abstract: The present study investigated the effect of the casting conditions for the reduced pressure test (RPT) on the melt quality of Al-Si alloy. The casting conditions considered in RPT were the atmospheric exposure during melting, sampling method, and mold pre-heating temperature. Density Index (DI) was measured to quantify the melt quality of the Al-Si alloy casted with the different casting conditions for the RPT. The sample with blocking atmospheric exposure during melting was 5.6% lower in DI than the one with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Jang et al found that increasing the mold pre-heating temperature increased the DI of an aluminum alloy up to a point after which further temperature increases decreased the DI. 50 In this study, the DI is included as monitored variables.…”
Section: Causes Of Porosity Defects In Lpdcmentioning
confidence: 99%
“…Jang et al found that increasing the mold pre-heating temperature increased the DI of an aluminum alloy up to a point after which further temperature increases decreased the DI. 50 In this study, the DI is included as monitored variables.…”
Section: Causes Of Porosity Defects In Lpdcmentioning
confidence: 99%
“…The addition of Si in commercial Al-Si-Mg alloys, such as Silafont™, Castasil™, Aural™, and Mercalloy™, induced a hypoeutectic or near-eutectic composition that ranges from 6.0 to 12 wt.%. Moreover, it is essential to ensure that the concentration of Mg does not exceed 0.7 wt.% because it is likely to significantly damage the mechanical properties of the alloy through the formation of brittle intermetallic phases that contain trace elements, such as Fe, Ni, and Cu [7][8][9]. Furthermore, the addition of Sr (0.01-0.02 wt.%) modifies the eutectic Si, thereby improving the ductility of the alloy.…”
Section: Introductionmentioning
confidence: 99%